P219 Migraine Is Associated with the Development of Inflammatory Bowel Disease: A Nationwide, Population-Based Study. (30th January 2023) - Lee, C; Han, K; Yu, H; Kim, S; Choi, K; Lee, H J; Koh, S J; Im, J P; Kim, J S
Abstract: Background: Inflammatory bowel disease (IBD) has been associated with an increased risk of migraine in a nationwide cohort sample analysis, but there is no evidence on the impact of migraine on the development of IBD The aim of this study was to determine the association between migraine and the development of IBD. Methods: This nationwide population-based cohort study was conducted using the Korean National Health Insurance Service (NHIS) database. A total of 10, 628, 070 people aged 20 years or older who had undergone a national health examination conducted by the NHIS in 2009 were followed up until 2017. The study population was divided into two groups according to the presence or absence of migraine. We analyzed the incidence of newly developed IBD, Crohn's disease (CD), or ulcerative colitis (UC) during the follow-up period. Results: The incidence of IBD was significantly higher in patients with migraine (adjusted hazard ratio [aHR] with 95% confidence interval [CI], 1.31 [1.173–1.468], p <0.001), CD (aHR with 95% CI, 1.58 [1.237–2.013], p <0.001) and UC (aHR with 95% CI, 1.26 [1.106–1.424], p <0.001) than those without migraine. After 5 years of follow-up in those with migraine, the curves implying cumulative incidences of IBD showed a steep increase especially for CD. In subgroup analysis, migraine was associated with the risk of UC in those with male sex (aHR, 1.431 vs. 1.117; interaction p = 0.042) Conclusion: Migraine is significantly associated with the development of IBD. Patients with migraine would be monitored carefully for the development of IBD.